Neutrophil-to-lymphocyte ratio as an independent predictor for unfavorable functional outcome in aneurysmal subarachnoid hemorrhage - Giede-Jeppe, Antje; Reichl, Jonathan; Sprügel, Maximilian; Lücking, Hannes; Hölter, Philip; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Huttner, Hagen; Gerner, Stefan (Journal of Neurosurgery, 2019)
OBJECTIVEStroke-associated immunosuppression and inflammation are increasingly recognized as factors triggering infections and thus potentially influencing outcome after stroke. Several studies have demonstrated that elevated neutrophil-to-lymphocyte ratio (NLR) is a significant predictor of adverse outcomes for patients with ischemic stroke or intracerebral hemorrhage. Thus far, in patients with subarachnoid hemorrhage the association between NLR and outcome is insufficiently established. The authors sought to investigate the association between NLR on admission and functional outcome in aneurysmal subarachnoid hemorrhage (aSAH).METHODSThis observational study included all consecutive aSAH patients admitted to a German tertiary center over a 5-year period (2008-2012). Data regarding patient demographics and clinical, laboratory, and in-hospital measures, as well as neuroradiological data, were retrieved from institutional databases. Functional outcome was assessed at 3 and 12 months using the modified Rankin Scale (mRS) score and categorized into favorable (mRS score 0-2) and unfavorable (mRS score 3-6). Patients' radiological and laboratory characteristics were compared between aSAH patients with favorable and those with unfavorable outcome at 3 months. In addition, multivariate analysis was conducted to investigate parameters independently associated with favorable outcome. Receiver operating characteristic (ROC) curve analysis was undertaken to identify the best cutoff for NLR to discriminate between favorable and unfavorable outcome in these patients. To account for imbalances in baseline characteristics, propensity score matching was carried out to assess the influence of NLR on outcome measures.RESULTSOverall, 319 patients with aSAH were included. Patients with unfavorable outcome at 3 months were older, had worse clinical status on admission (Glasgow Coma Scale score and Hunt and Hess grade), greater amount of subarachnoidal and intraventricular hemorrhage (modified Fisher Scale grade and Graeb score), and higher rates of infectious complications (pneumonia and sepsis). A significantly higher NLR on admission was observed in patients with unfavorable outcome according to mRS score (median [IQR] NLR 5.8 [3.0-10.0] for mRS score 0-2 vs NLR 8.3 [4.5-12.6] for mRS score 3-6; p < 0.001). After adjustments, NLR on admission remained a significant predictor for unfavorable outcome in SAH patients (OR [95% CI] 1.014 [1.001-1.027]; p = 0.028). In ROC analysis, an NLR of 7.05 was identified as the best cutoff value to discriminate between favorable and unfavorable outcome (area under the curve = 0.614, p < 0.001, Youden's index = 0.211; mRS score 3-6: 94/153 [61.4%] for NLR ≥ 7.05 vs 67/166 [40.4%] for NLR < 7.05; p < 0.001). Subanalysis of patients with NLR levels ≥ 7.05 vs < 7.05, performed using 2 propensity score-matched cohorts (n = 133 patients in each group), revealed an increased proportion of patients with unfavorable functional outcome at 3 months in patients with NLR ≥ 7.05 (mRS score 3-6 at 3 months: NLR ≥ 7.05 82/133 [61.7%] vs NLR < 7.05 62/133 [46.6%]; p = 0.014), yet without differences in mortality at 3 months (NLR ≥ 7.05 37/133 [27.8%] vs NLR < 7.05 27/133 [20.3%]; p = 0.131).CONCLUSIONSAmong aSAH patients, NLR represents an independent parameter associated with unfavorable functional outcome. Whether the impact of NLR on functional outcome is related to preexisting comorbidities or represents independent causal relationships in the context of stroke-associated immunosuppression should be investigated in future studies.
EVALuna2:204508